(untitled) (Theatrum historiae, 2010)
The First World War struck the north-eastern part of the Austro-Hungarian monarchy, Halič and Bukovina, where the great majority of the population consisted of Jews. The battles on the eastern front at the beginning of the war forced the largest wave of refugees inwards into the Austro-Hungarian monarchy in two directions, along the main railway lines running southwest through Hungary to Vienna and northwest via Přemyšl and Kraków into Moravia, Bohemia, and Austria. After the asylum camps in Moravia had filled up by the beginning of November 1914, the new influx of refugees left for Bohemia, where their stay was funded by the Habsburg monarchy through its political offices. In Bohemia the Jewish refugees were placed in all the political districts that existed at that time, in large cities as well as in small villages. The state provided the refugees with maintenance support, which was increased several times during the First World War. Jewish trusts and charitable associations also provided a great deal of assistance. The refugees were housed in all kinds of vacant premises and rooms imaginable. This accommodation often did not even have basic hygiene facilities. To prevent the spread of infectious diseases, the refugees were vaccinated, given medical checkups and inspected to ensure they were clean. The refugee children went to the local schools or special schools were set up for them. Everyone, not just the Jewish refugees, was exhorted to work by threats that their state benefits would be stopped. They worked in factories, helped out on farms and in households, or made a living by doing craftwork. Some refugees were drafted into the army if they were the right age. Relations between the refugees and the resident population, including the local assimilated Jews, varied from place to place in Bohemia and changed often during the war. The Jewish refugees were constantly being forced by the central authorities to repatriate or to voluntarily return to their homes in Halič and Bukovina. New refugees came to replace them, however, released from refugee camps in Bohemia and Moravia. These waves of emigrants and immigrants meant that the number of refugees in the different towns and villages was continually changing, so it is not possible to say exactly how many refugees there were in a particular area. On October 28th 1918 the Republic of Czechoslovakia was established. All refugees, regardless of nationality or creed, had to be repatriated back to their homeland by the end of 1919. The Jewish refugees from Halič and Bukovina had both a positive and negative influence on the life of the people of Bohemia, and thus played a significant role in the history of Bohemia during the First World War and for several years after it.